Determinants of nutrition status among adolescents in selected secondary schools in rural Kanungu district Uganda - Angella, Natukunda; Kariuki, John; Nyamai, Joseph Juma (International Journal Of Community Medicine And Public Health, 2024)
Background: Adolescence, the time between childhood and adulthood, often considered relatively healthy stage of life remain highly vulnerable to malnutrition. One crucial first step in reducing teenage malnutrition may be to attend to their dietary needs. This study examined the determinants of nutrition status among secondary school adolescents in the Kanungu district, Uganda. Methods: A school-based cross-sectional analytical study was employed in this study where both qualitative and quantitative methods of data collection were used for triangulation purposes. A multi-stage random sampling method was applied to obtain the study respondents. The Cochran formula was utilized to obtain 340 study respondents. Results: More than a quarter (37.1%) of the study respondents had malnutrition. Households that were father-headed (OR=1.8,95%CI=1.03-3.20), having met the recommended number of meal frequency (OR=2, 95%CI=1.13-3.44), being aware of healthy dietary habits (OR=2.2, 95%CI=0.29-0.71), having a small household size of 1-4 members (OR=4.3, 95%CI=2.38-7.83) and being employed (OR=2.1, 95%CI=1.17-3.93) increased the odds of having a normal nutrition status while having a primary level of education (OR=3.6, 95%CI=0.11-0.68), having an inadequate dietary score (OR=2.1,95%CI=0.28-0.76) reduced the odds of having a normal nutrition status. Conclusions: From this study, malnutrition was a public health concern. Households that were father-headed, being aware of healthy dietary habits, having a small household size of 1-4 members, and being employed increased the odds of having a normal nutrition status while having a primary level of education, having an inadequate dietary score reduced the odds of having a normal nutrition status.